2023
DOI: 10.1101/2023.09.07.23295154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interim influenza vaccine effectiveness estimates during the 2023 Southern Hemisphere season

J Gonzalo Acevedo-Rodriguez,
Carlos Zamudio,
Noah Kojima
et al.

Abstract: Our findings suggest that a substantial number of people sought care for CLI during an early Southern Hemisphere season during which A/H1N1pdm09 clade 6B.1A.5a.2a viruses predominated. The minority vaccinated benefitted from the A/Victoria/2570/2019 (H1N1)pdm09-like antigen which afforded good protection against illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The result of the influenza A(H1N1)pdm09 phylogenetic tree with altered amino acid sequences suggests that the vaccine may be less effective against A(H1N1)pdm09 in Pakistan. Additionally, between September 13, 2022, and January 25, 2023, the US Centers for Disease Control and Prevention (CDC) revealed that the vaccination was 54% effective against laboratory‐confirmed influenza A in inpatient and emergency department (ED) settings 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…The result of the influenza A(H1N1)pdm09 phylogenetic tree with altered amino acid sequences suggests that the vaccine may be less effective against A(H1N1)pdm09 in Pakistan. Additionally, between September 13, 2022, and January 25, 2023, the US Centers for Disease Control and Prevention (CDC) revealed that the vaccination was 54% effective against laboratory‐confirmed influenza A in inpatient and emergency department (ED) settings 30,31 …”
Section: Discussionmentioning
confidence: 99%